Orthodontic treatment of unilateral cleft lip and palate associated with maxillary canine/premolar transposition: case report - Rodrigo Matos de Souza; Henrique Telles de Oliveira; Marcel Marchiori Farret (Dental Press Editora, 2020)
ABSTRACT Introduction: The cleft lip and palate is the most frequent craniofacial anomaly and as a consequence of this malformation some inadequate occlusal relationship between the arches are observed. Furthermore, dental absences, individual positioning changes of teeth as rotations, and in more rare situations the transpositions may be found as well. Description: In this context, in this article is reported a case of a 9-year-old patient with unilateral cleft lip and palate, with anterior and posterior crossbite on the left side, absence of the maxillary left lateral incisor, and transposition of the maxillary left canine and first premolar. The patient was treated with slow maxillary expansion, secondary graft and fixed orthodontic appliance, transposition maintenance and closing of the lateral incisor space with the first premolar, by means of mesialization of the posterior teeth. Results: At the end of the treatment, good intercuspation and an important aesthetic gain for the patient were achieved. The analysis three years after treatment revealed a good stability of the results obtained.